2021
DOI: 10.1093/jbcr/irab128
|View full text |Cite
|
Sign up to set email alerts
|

The Patient’s Perspective: Burn Reconstructive Surgery During the COVID-19 Pandemic

Abstract: During the Covid-19 pandemic, hospital systems delayed or halted elective surgeries and outpatient care, profoundly disrupting reconstructive burn treatment ranging from surgery to postoperative therapy. This study aims to characterize burn patients’ perspectives on reconstructive surgery during Covid-19. A 12-component questionnaire to burn patients awaiting reconstructive surgery at a single ABA verified Burn Center was administered. Responses regarding willingness to undergo reconstruction, perceived medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Despite this, 83% of respondents strongly preferred to resume surgical and therapeutic care delayed because of the pandemic. 69 Awareness and management of barriers to care continue to be a long-term challenge of the pandemic.…”
Section: Burn Managementmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite this, 83% of respondents strongly preferred to resume surgical and therapeutic care delayed because of the pandemic. 69 Awareness and management of barriers to care continue to be a long-term challenge of the pandemic.…”
Section: Burn Managementmentioning
confidence: 99%
“…68 Aside from the medical outcomes, a survey study examined patient perspectives on burn reconstructive surgery during the pandemic. 69 Forty-three percent of respondents were pediatric. 69 It showed that the COVID-19 pandemic contributed to additional stressors in their burn treatment, including financial elements and difficulty attaining care.…”
Section: Burn Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group and others have previously demonstrated the impact on outpatient care, admissions and acute surgical resources, and described initiatives to replace in-person with virtual consultation whenever possible. 7,9,10 For vulnerable patient populations with suboptimal access to surgical care, the pandemic has resulted in exacerbation of pressure injuries, and delays in definitive care for NSTI, and care may have been provided in environments unfamiliar or ill-equipped to provide the kind of holistic management available at a multidisciplinary burn centre. 1113 Reduced opportunities for trainees to participate in surgery for complex wounds and scars have also been evident, and may further entrench a system favouring sub-speciality over general plastic surgery practice.…”
mentioning
confidence: 99%